Effect of Financial Sector Development on Poverty Alleviation - The Nigerian Experience (1986 – 2018) - Onwuka, Ifeanyi Onuka; Nwadiubu, Anthony (Advances in Social Sciences Research Journal, 2019)
The study examined the impact of financial sector development on investment in government treasury bills in Nigeria. Financial sector development was proxied by the ratio of money supply to GDP (M2/GDP); private sector credit to GDP (CPS/GDP) and lending interest rate while the dependent variable was measured by the outstanding treasury bills in money market. The study adopted the ex-post facto research design. The study adopted the multiple regression technique while the result of the regression coefficient was subjected to diagnostic tests. The result of the study showed that the level of intermediation and lending interest rate had significant effect on investment in treasury bills in Nigeria as a unit increase in interest rate resulted in 52 percent increase in treasury bills. Also a unit increase in lending rate of banks led to 11 percent increase in investment in treasury bills in Nigeria. Based on the results, the study recommended a systematic reduction in lending interest rates and increase in savings rate to stimulate high investment returns to savers and reduce the credit risk on lending